Axenfeld Rieger Syndrome: an unusual case report: Poster Presentation - Case Report - Resident - RAHMADIANSYAH, MUHAMMAD FADHIL; SAYUTI, KEMALA (Majalah Oftalmologi Indonesia, 2023)
Introduction : Axenfeld-Rieger Syndrome (ARS) is a rare autosomal dominant disorder that characterized by ocular manifestation, especially the cornea, iris, glaucoma, and systemic abnormalities in teeth, face, abdomen, heart and genitals. Case Illustration : A 7-year-old boy patient presented to policlinic with complaint of blurry vision in both eyes. No other abnormalities in history. On examination, visual acuity of right eye 5/60 and left eye 4/60. Slit lamp examination revealed hypoplasia iris, corectopia, and polycoria. Intraocular pressure (IOP) on right eye 25 mmHg and left eye 24 mmHg. Non ocular manifestation were flat face and teeth deformity. This patient was diagnosed ARS with secondary glaucoma. We managed the patient together with the dental and pediatric department in order to confirm and treat any systemic abnormality. Patient underwent cycloplegic refractive correction to achieve best corrected visual acuity right eye 20/200 and left eye 20/150 (LEA chart). Timolol 0,25% eye drop was given twice a day with IOP right eye 19 mmHg and left eye 20 mmHg after 2 weeks. Discussion : The diagnosis of patient was ARS with secondary glaucoma. The patients with ARS have a 50% lifetime risk of glaucoma. Comprehensive management to confirm and treat the systemic abnormalities from dental and pediatric departments was important. Management in our department includes correction of refractive errors and lowering of IOP. Conclusion : Axenfeld Rieger Syndrome that manifest ocular and non-ocular need to investigated thoroughly. Multidisciplinary contribution of this case is necessary to maintain the ocular stabilization and prevent any harm from systemic abnormalities.